Upaya Menumbuhkan Minat Belajar Membaca Al-Qur’an pada Anak Usia 10–15 Tahun di Madin Al–Muttaqiin Gedangsari, Gunungkidul - Sriyanta, Sriyanta; Subando, Joko (Lembaga Yasin AlSys, 2025)
Islamic Religious Education plays a vital role in shaping the religious character and personality of children from an early age, in line with Islamic teachings that encompass all aspects of life. This study aims to examine the urgency of Islamic Religious Education, particularly within non-formal educational institutions such as Madrasah Diniyah (Madin) Al–Muttaqiin in Gedangsari, Gunungkidul, which holds a strategic role in instilling religious values in children. The research employed a qualitative field approach, with data collected through observation, in-depth interviews, and documentation. The findings indicate that students’ learning interest is a key factor in the effectiveness of religious education. The educational process structured around learning categories, instructional objectives, and learning elements grounded in the Qur’an as the primary source of Islamic teachings serves as a crucial foundation for developing religious values. Early childhood is regarded as the most strategic phase for instilling such values; therefore, the learning approach must be gentle, enjoyable, and nurturing. The study concludes that synergy among formal education, non-formal institutions, and families is essential to successfully cultivating a generation that is faithful, knowledgeable, and morally upright.